Building Trust in Digital Retail: How Customer Reviews, Website Quality, and Product Assortment Shape Online Purchase Intention at Indomaret Yogyakarta - Clara Rosita Apsari; Dyah Sugandini; Wisnalmawati Wisnalmawati (CV. Doki Course and Training, 2026)
This study investigates the effects of customer reviews, website quality, and product assortment on online purchase intention, with trust as a mediating variable, among Klik Indomaret users in Yogyakarta. Using a quantitative approach and SEM-PLS with 209 respondents, the findings show that customer reviews and website quality significantly enhance online purchase intention, while product assortment has no direct effect. Trust plays a crucial role, exerting a significant positive influence on online purchase intention and mediating the effects of website quality and product assortment, but not customer reviews. These results indicate that system performance, usability, and product reliability are more influential than assortment variety within convenience-store digital platforms. The study contributes to understanding online consumer behaviour and highlights the importance of improving platform stability, interface design, and product availability to strengthen trust and encourage online purchasing. Practical recommendations and directions for future research are also provided